Simvastatin Therapy for Drug Repositioning to Reduce the Risk of Prostate Cancer Mortality in Patients With Hyperlipidemia - Chen, Yu-An; Lin, Ying-Ju; Lin, Cheng-Li; Lin, Hwai-Jeng; Wu, Hua-Shan; Hsu, Hui-Ying; Sun, Yu-Chen; Wu, Hui-Yu; Lai, Chih-Ho; Kao, Chia-Hung (Frontiers in Pharmacology, 2018)
Prostate cancer (PCa) is one of the most commonly diagnosed cancers in the western world, and the mortality rate from PCa in Asia has been increasing recently. Statins are potent inhibitors of 3-hydroxy-3-methyl glutaryl coenzyme A (HMG-CoA) reductase and are commonly used for treating hyperlipidemia, with beneficial effects for cardiovascular disease and they also exhibit anti-cancer activity. However, the protective effects of statins against PCa are controversial. In this study, we investigated the effect of two types of statins (simvastatin and lovastatin) and the mortality rate of PCa patients by using the Taiwan National Health Insurance Research Database (NHIRD). A total of 15,264 PCa patients with hyperlipidemia records and medical claims from the Registry of Catastrophic Illness were enrolled. The patients were divided into two cohorts based on their statin use before the diagnosis of PCa: statin users (n = 1,827) and non-statin users (n = 1,826). The results showed that patients who used statins exhibited a significantly reduced risk of mortality from PCa (adjusted hazard ratio [HR] = 0.84, 95% CI = 0.73–0.97). Analysis of the cumulative defined daily dose (DDD) indicated that patients who were prescribed simvastatin ≥180 DDD had a dramatically decreased risk of death from PCa (adjusted HR  = 0.63; 95% CI  =  0.51–0.77). This population-based cohort study demonstrated that statin use significantly decreased the mortality of PCa patients, and that this risk was inversely associated with the cumulative DDD of simvastatin therapy. The results of this study revealed that statins may be used for drug repositioning and in the development of a feasible approach to prevent death from PCa.